Factors Influencing Technopreneurial Intention among University Students in West Jakarta - Anggraini, Agnes Clarissa; Rodhiah (Journal of Social Science and Business Studies, 2026)
This study seeks to examine the influence of information and communication technology (ICT) self-efficacy, technopreneurial learning, and individual entrepreneurial orientation (Individual EO) on the technopreneurial intentions of university students in West Jakarta. The population comprises university students in West Jakarta who demonstrate an interest in entrepreneurship, particularly in technology driven ventures. A total of 130 respondents were selected through purposive sampling, with the criteria that participants must be students enrolled in universities in West Jakarta and have an interest in technopreneurial activities. Data were gathered using online Likert-scale questionnaires distributed via Google Forms, which were adapted from previously validated and reliable instruments. The data were then analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4.1.1.6 software. The findings reveal that ICT self-efficacy has a positive but statistically insignificant effect on technopreneurial intention. In contrast, technopreneurial learning demonstrates a positive and significant effect on technopreneurial intention. Similarly, Individual EO is found to have a positive and significant influence on technopreneurial intention. In summary, although ICT self-efficacy does not have a direct significant impact, both technopreneurial learning and Individual EO play crucial roles in shaping technopreneurial intention among university students in West Jakarta.